Inhibition of ribosome assembly factor PNO1 by CRISPR/Cas9 technique suppresses lung adenocarcinoma and Notch pathway: Clinical application. Issue 3 (10th January 2023) - Roy, Sanjit K.; Srivastava, Shivam; Hancock, Andrew; Shrivastava, Anju; Morvant, Jason; Shankar, Sharmila; Srivastava, Rakesh K.
Abstract: Growth is crucially controlled by the functional ribosomes available in cells. To meet the enhanced energy demand, cancer cells re‐wire and increase their ribosome biogenesis. The RNA‐binding protein PNO1, a ribosome assembly factor, plays an essential role in ribosome biogenesis. The purpose of this study was to examine whether PNO1 can be used as a biomarker for lung adenocarcinoma and also examine the molecular mechanisms by which PNO1 knockdown by CRISPR/Cas9 inhibited growth and epithelial–mesenchymal transition (EMT). The expression of PNO1 was significantly higher in lung adenocarcinoma compared to normal lung tissues. PNO1 expression in lung adenocarcinoma patients increased with stage, nodal metastasis, and smoking. Lung adenocarcinoma tissues from males expressed higher PNO1 than those from females. Furthermore, lung adenocarcinoma tissues with mutant Tp53 expressed higher PNO1 than those with wild‐type Tp53, suggesting the influence of Tp53 status on PNO1 expression. PNO1 knockdown inhibited cell viability, colony formation, and EMT, and induced apoptosis. Since dysregulated signalling through the Notch receptors promotes lung adenocarcinoma, we measured the effects of PNO1 inhibition on the Notch pathway. PNO1 knockdown inhibited Notch signalling by suppressing the expression of Notch receptors, their ligands, and downstream targets. PNO1 knockdown also suppressed CCND1, p21, PTGS‐2, IL‐1α, IL‐8, and CXCL‐8 genes. Overall, our data suggest that PNO1 can be used as a diagnostic biomarker, and also can be an attractive therapeutic target for the treatment of lung adenocarcinoma.